Tribute to Evan Weissman on behalf of the Syracuse-Onondaga Food Systems Alliance - Maura Ackerman; Mary Carney; Brandy Colebrook; Nel Gaudé; Elissa Johnson; LaToya Jones; David Knapp; Jessi Lyons; Peter Ricardo; Jonnell Robinson; Rachel Viens; Curtis Waterman (Journal of Agriculture, Food Systems, and Community Development, 2021)
First paragraphs: